2011
DOI: 10.1017/s1751731110001801
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome-wide QTL study on BTA29 affecting temperament traits in German Angus beef cattle and mapping of DRD4

Abstract: The behaviour of beef cattle is important for the safety and welfare of stockmen and animals. Ten microsatellites spanning BTA29 and, in addition, the candidate gene, dopamine receptor D4 gene, were analysed in 545 German Angus calves of six sires and included in a quantitative trait locus (QTL) study on the basis of three different behaviour tests. A putative QTL for the score while entering the scale (ScE) was detected at BMS764. The DRD4 fragment was mapped in the distal region of BTA29 15.3 cM distal of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Aberrations concerning rearing conditions and cattle breeds (Hoppe et al, 2010) as well as different evaluations of behaviour phenotypes and different marker densities complicate the comparability between studies and must be taken into account. Nevertheless, overlapping QTL were found between the studies, especially on BTA29 (Hiendleder et al, 2003;Gutiérrez-Gil et al, 2008;Glenske et al, 2011).…”
Section: Genomic Regions Associated With Temperament Traitsmentioning
confidence: 93%
See 1 more Smart Citation
“…Aberrations concerning rearing conditions and cattle breeds (Hoppe et al, 2010) as well as different evaluations of behaviour phenotypes and different marker densities complicate the comparability between studies and must be taken into account. Nevertheless, overlapping QTL were found between the studies, especially on BTA29 (Hiendleder et al, 2003;Gutiérrez-Gil et al, 2008;Glenske et al, 2011).…”
Section: Genomic Regions Associated With Temperament Traitsmentioning
confidence: 93%
“…A prominent candidate gene, the dopamine receptor D4 gene (DRD4) has been associated with behavioural traits like novelty seeking and curiosity in humans and different animals (Bailey et al, 2007;Munafò et al, 2008;Korsten et al, 2010). In cattle, DRD4 can be mapped to the distal part of BTA29 (Glenske et al, 2011), but no QTL or direct association for temperament in cattle have been identified in this region so far. Another widely discussed functional candidate gene is the monoamine oxidase A (MAO A) gene, which degrades catecholamines like serotonin, norepinephrine and dopamine (Shih et al, 1999).…”
Section: Candidate Genesmentioning
confidence: 99%
“…Moreover, Glenske et al (2011) reported a low relationship between the dopamine receptor D4 (DRD4) gene located near QTL for behavioural traits on chromosome 29, and temperament of German Angus cattle. A study using the expression of the leucocyte heat shock protein (Hsp) gene for early detection of the subclinical signs of bovine respiratory disease complex (BRD) confirmed that this gene is associated with stress response of animals (Eitam et al, 2010).…”
Section: Candidate Genes For Behavioural Traits In Cattlementioning
confidence: 99%
“…A significant observation in our study of this marker is that, even though there is no significant specific allele segregation between the genetic groups, the distribution of allelic frequencies indicated that allele G was the most frequent in the B. t. indicus breeds, while allele T was most frequent in B. t. taurus breeds. This distribution pattern is interesting from a phenotypic point of view because Glenske et al (2011) found that genotype TT was associated with lower curiosity scores in the German Angus breed. Curiosity is a trait related with social behavior including novelty seeking (Momozawa et al, 2005).…”
Section: Resultsmentioning
confidence: 80%
“…Due to the absence of complete reported nucleotide sequences for DRD4 gene, we genotyped the SNP located at intron 1 of bovine DRD4 gene previously reported by Glenske et al (2011). DNA from these samples and an additional 199 bovine hair samples obtained from different herds and breeds (B. t. taurus: Holstein, Charolais, Simmental, Lidia, and Wagyu; B. t. indicus: Brahman, Gyr, Sardo Negro, Guzerat, and Indubrasil) located at Mexico, was isolated using the Wizard® genomic DNA purification kit (Promega Corporation, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%